Acceptance and usage of social media as a platform among student entrepreneurs. Issue 2 (15th May 2017) - Nawi, Noorshella Binti Che; Mamun, Abdullah Al; Nasir, Noorul Azwin Binti Md; Shokery, Noorlisa Maria bt A. Hamid; Raston, Nursalihah Binti Ahmad; Fazal, Syed Ali
Abstract : Purpose: While it is perceived that adoption reflects acceptance, the purpose of this paper is to argue that individual usage is critical and cannot be guaranteed by mere adoption. This study, therefore, focuses on the factors (i.e. performance expectancy, perceived trust, perceived risk, facilitating condition, and perceived enjoyment) contributing to the adoption and ultimately usage of social media as a business platform among student entrepreneurs in Malaysia under the premise of the unified theory of acceptance and use of technology (UTAUT). Design/methodology/approach: This study adopts a cross-sectional design and quantitative data are collected from 300 selected respondents listed as student entrepreneurs in the entrepreneurship centers of all public universities within Peninsular Malaysia. Findings: Performance expectancy, perceived risk, perceived trust, and perceived enjoyment have a significant effect on the adoption of social media leading to its usage as a business platform. Findings also report a significant mediating effect of adoption of social media on the relationship between performance expectancy, perceived trust, perceived risk, and perceived enjoyment with the depth of social media usage. Research limitations/implications: In order to promote entrepreneurial activities among student entrepreneurs using social media as a business platform, programs and policies should focus on improving cyber security and value-added services. Originality/value: This study puts forward and tests the original UTAUT model to assess the adoption and depth of social media usage as a business platform among young student entrepreneurs in Peninsular Malaysia, which provides a foundation for the design and implementation of programs and policies that promote entrepreneurial activities using social media among student entrepreneurs in Malaysia.